Trick or Treat? Licorice-Induced Hypokalemia: A Case Report - Benge, Elizabeth (Cureus, 2020)
The by-products of black licorice metabolism are toxic in high concentrations. Patients who consume large quantities of black licorice are at risk of developing an acquired syndrome of apparent mineralocorticoid excess. This presents clinically as hypertension, hypernatremia, and hypokalemia. Here, we present the unique case of a 74-year-old woman with a past medical history of neurogenic orthostatic hypotension, on fludrocortisone, who presented to the emergency department with asymptomatic hypokalemia (2.4 mmol/L) as detected in outpatient laboratory studies. During her hospital stay, it was discovered that the patient was consuming excessive amounts of black licorice. With this information, the synergistic interaction of fludrocortisone and black licorice was recognized as the cause of the patient’s severe hypokalemia. The patient’s fludrocortisone was stopped and she was treated with multiple courses of potassium repletion. Upon discharge, her fludrocortisone was discontinued, and she was prescribed midodrine to treat her neurogenic orthostatic hypertension. While small amounts of black licorice are safe, excessive licorice consumption can cause severe disease. Our case presents an opportunity to appreciate the plethora of etiologies for severe hypokalemia and the importance of taking a thorough patient history to avoid potentially fatal clinical outcomes.